A Comparative Evaluation of the Physical and Chemical Characteristics of Composted Tea Tree (Melaleuca alternifolia L.) with Pine Bark Growing Media in Tobacco (Nicotiana tabucum L.) Seedling Production - Johnson Masaka; Noel Chimwanda; Ignatius Chagonda; Misheck Chandiposha (Advances in Agriculture)
The search for suitable organic growing media substitutes for pine bark based media combinations has been prompted by concerns over high costs and lack of availability to smallholder farmers coupled with increasing demand for soilless media in Zimbabwe. A trial was conducted for 12 weeks to investigate the suitability of tea tree compost-based substrates for tobacco seedling production as a substitute of the traditional pine bark growing media. The use of composted tea tree growing media in float trays significantly (p<0.05) increases the bulk density of the media by 23–59% when compared with pine bark media. The cation exchange capacity of the native pine bark growing media was 14 to 95% lower than that for the composted tea tree media. The use of the composted tea as media for tobacco seedling nursery reduced seed germination by 10–37%, seedling stem height by 4–34%, and seedling stem girth by 6–175%. While the nutrient holding and supplying potential of the growing media in seedling production is important for normal seedling growth, its effect on seedling growth vigor is less important than that exerted by the presence of suitable physical conditions in the media.